PENGATURAN PENDAFTARAN PENDIRIAN CV BERDASARKAN KUHD DAN PERATURAN MENTERI HUKUM DAN HAK ASASI MANUSIA NOMOR 17 TAHUN 2018 - Anak Agung Kompiang Gede; A.A.Sagung Ngurah Indradewi (Kerta Dyatmika, 2021)
This research is motivated by the existence of conflicting norms about the registration arrangements for the establishment of Commanditaire Vennotschap (CV). According Article 23 of the Commercial Law Code, the deed of establishment of the Vennotschap Commanditaire (CV) and Article 3 of the Minister of Law and Human Rights Regulation No. 17 of 2018. The problem studied is: (1) How do the registration arrangements for the establishment of a CV be reviewed from the KUHD and Minister of Law and Human Rights Regulation Number 17 of 2018 ?. (2) What are the legal consequences if the provisions of Article 3 of the Minister of Law and Human Rights Number 17 of 2018 are not implemented in the process of establishing a CV?. The type of research used is normative legal research using a statutory approach and an analytical conceptual approach. Based on the results of the study it can be seen that: (1) CV establishment registration arrangements in terms of the KUHD and Minister of Law and Human Rights Regulation Number 17 of 2018 according to norm conflicts between the Minister of Law and Human Rights Regulation No. 17 of 2018 with the KUHD, it is necessary to review the position of each of these laws and regulations. In a hierarchical regulation, the Minister of Law and Human Rights Regulation No. 17 of 2018 has a lower position than the KUHD. The legal consequence is that the Regulation of the Minister of Law and Human Rights Number 17 Year 2018 cannot rule out the KUHD, so the obligations / arrangements contained in the KUHD for the sake of law must be considered to remain valid. (2). Legal consequences if the CV does not implement the provisions of Article 3 of the Minister of Law and Human Rights Regulation No. 17 of 2018 is that there are no legal consequences in the Minister of Law and Human Rights Regulation No. 17 of 2018. This can prove that the regulation cannot provide legal certainty for the community.